Sistem Informasi Ekspedisi Barang Pada PT. New Power Global Energy Dengan Menggunakan Metode Extreme Programming - John Roni Coyanda; Nining Ariati; Hastha Sunardi; K.Ghazali K.Ghazali (Jurnal Informatika Global, 2022)
PT New Power Global Energy (NPGE) is a company engaged in freight forwarding services. In its businessprocess, New Power Global Energy is not utilizing technology. To manage all information on shipping goods, an information delivery system is needed so that information is easily understood and traced. The system that is built is The Extreme Programming method is a model that is included in the agile approach introduced by Kent Back. According to his explanation, the definition of XP is as follows: "Extreme Programming (XP) is a fast, efficient, low-risk, flexible, predictable, scientific, and fun software development method because system performance assessmentsare needed in a fast time while there are still system needs that are still needed. changes, this model tends to use an Object-Oriented approach. The stages that must be passed include: Planning, Design, Coding, and Testing. Extreme Programming's target is a small to medium-sized team, no need to use a large team expected to help the admin and director in managing information on shipping goods starting from sending, receiving and making reports. This application is designed using the it using the Extreme Programming Methods because the assessment systemperformance is needed in a fast time while there are system requirements that are still changing, and for the system, we use an supporting application which is laravel framework, programming language using JavaScript and PHP and MySQL as an database. The result of design is an system that can process admin performance data quickly, provide performance information MySQL for the database. with management of shipping data features, managing goods delivery status, goods receipt feature, item barcode feature, tracking feature. Keyword: Information System, Expedition, XP